Value Innovation as a Wealth Creation Tool - Elayache, Reem (2012)
Lebanon is one of the most popular tourist destinations in the Middle East. Due to its nature and culture as it is known for its moderate Mediterranean climate and green environment. Also the Lebanese culture is a combination of various civilizations and religions which provide the country with a unique culture. However, Lebanon was under the shadow of civil war for almost 15 years, this destroyed the economy of the country. It led to a rapid drop of more than 50% of the GDP and resulted in Lebanon losing its position as the preferred port that links Middle East to the western countries. Also Lebanon was known as the Middle East banking centre. In the current scenario Lebanon is in the process of re-establishing itself which opens up new opportunities for new businesses especially in the tourism and service sectors. These two sectors are considered to have the highest contribution to the Lebanese economy. This has led to an increase in the importance of the foodservice sector. Lebanese people are very sociable and always like to try different kinds of food and experience new things. And since Lebanon is a tourism country, this makes the restaurants business very attractive and at the same time makes the foodservices industry in Lebanon very competitive. So due to the vast options of restaurants for customers, restaurants’ management should always be up to date and provide them with new experiences. Most of the restaurants in Lebanon are known for their high standard of quality and mostly all the cuisines are available. However, what distinguishes a restaurant from another is the service offered. The restaurants’ owners insist on hiring highly qualified management with significant experience in managing such organizations. As a result the management always ensures employing skilled staff with academic and practical qualifications. This report emphasises on the importance of using innovation, especially in services, to ensure survival and increasing profit for firms, particularly restaurants. Also this paper focuses on presenting value innovation as the main source of wealth creation for companies. Moreover, a model that can be used by companies to enhance innovation will be presented. This report also highlights the critical role that can be played by the top management to facilitate and enhance creativity and innovation inside the organization. The aim of this paper is to find out how organizations especially restaurants in Lebanon can apply creativity and innovation for offering new services to the customers. This would enable the organizations to create a new market place for them in the competitive Lebanese foodservice sector. In addition to create wealth the restaurants are also looking for survival, growth and sustainability.